ASSESSING THE POTENTIAL COMPENSATION PRESSURE OSCILLATIONS IN A NETWORK OF EXISTING PUMPING EQUIPMENT WHILE DRIVING THEIR WORK - , М. О., В. І., О. Г. (Municipal economy of cities. Series: «Economy science», 2013)
The paper analyzes the technical characteristics of the pumping equipment on the possibility of compensation for existing differential pressure in water supply networks.